(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Impunity and corruption are always present scourges in the administration of justice. The lack of technical capacity of the prosecutor in the preliminary and trial hearings generates impunity in many cases and in other cases it is generated by corruption. This article addresses this issue through a case method whose central activity is the analysis of said problems present in the hearings. The purpose is to give meaning to the federal constitutional norm when it establishes in its section I, section A, of article 20, "the criminal process will have as its object the clarification of the facts, protect the innocent, and ensure that the guilty do not go unpunished." The analysis arises from professional practice; the hypothesis consists in sustaining the need to justify the substitution of the prosecutor in the accusatory criminal system in Mexico through the principles of the system itself. The figure of the prosecutor as a technical body must be addressed, for which it is necessary to expose mechanisms that allow the judge this substitution in the meantime it is explicitly established in the norm.